Rancangan Sistem Penilaian Kinerja Divisi Marketing Menggunakan Human Resource Analytic - Caroline, Angela; Fernando, Rio (Jurnal Manajemen dan Bisnis Kreatif, 2024)
Employees are the core of any successful business, and their skills are critical to achievingcompany goals. This research focuses on improving performance management in the salesand marketing department of Hotel BC. By carefully examining the core competencies ofthe sales and marketing team, this research aims to develop a performance evaluationsystem that accurately reflects employee contributions. This system will utilize thestrengths of human resource information systems and data analysis. Our research usedan analytical descriptive approach to understand the current performance evaluationprocess and identify areas for improvement. Preliminary findings indicate that work ethic,sales achievement, and company loyalty are important factors in assessing theperformance of marketing staff. While these factors may evolve as the hotel develops, it isimperative to maintain a rigorous and systematic approach to performance evaluation.